2019
DOI: 10.15252/embr.201847483
|View full text |Cite
|
Sign up to set email alerts
|

Reporter‐based fate mapping in human kidney organoids confirms nephron lineage relationships and reveals synchronous nephron formation

Abstract: Nephron formation continues throughout kidney morphogenesis in both mice and humans. Lineage tracing studies in mice identified a self‐renewing Six2‐expressing nephron progenitor population able to give rise to the full complement of nephrons throughout kidney morphogenesis. To investigate the origin of nephrons within human pluripotent stem cell‐derived kidney organoids, we performed a similar fate‐mapping analysis of the SIX2‐expressing lineage in induced pluripotent stem cell (iPSC)‐derived kidney organoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(117 citation statements)
references
References 40 publications
3
113
1
Order By: Relevance
“…Indeed, we have now definitively shown that the nephron epithelium arising in our kidney organoids comes from a SIX2-expressing nephron progenitor, as anticipated based upon our understanding of nephron formation in the mouse (Fig. 3OP; Howden et al 2019).…”
Section: Building a Kidney Organoid From Pluripotent Stem Cellssupporting
confidence: 65%
See 4 more Smart Citations
“…Indeed, we have now definitively shown that the nephron epithelium arising in our kidney organoids comes from a SIX2-expressing nephron progenitor, as anticipated based upon our understanding of nephron formation in the mouse (Fig. 3OP; Howden et al 2019).…”
Section: Building a Kidney Organoid From Pluripotent Stem Cellssupporting
confidence: 65%
“…However, induction at day 18 resulted in the identification of a stromal SIX2-derived population but no evidence of ongoing nephrogenesis ( Fig. 3P; Howden et al 2019). Indeed, it is possible that there are distinct SIX2-expressing populations arising at this time that may represent off-target cell types, such a muscle progenitors.…”
Section: Accurate Lineage But Precocious Cessation Of Nephrogenesis Wmentioning
confidence: 99%
See 3 more Smart Citations